Attracting international spectators to a sport event held in Asia: The case of Formula One Petronas Malaysia Grand Prix. Issue 2 (8th May 2018) - Watanabe, Yasuhiro; Gilbert, Cassendra; Aman, Mohd Salleh; Zhang, James J.
Abstract : Purpose: The purpose of this paper is to examine the systematic influence of core product features, event operation quality, sport fan identification, and image of host city as a tourism destination on behavioral intentions of international spectator at a Formula One (F1) event held in Malaysia. Design/methodology/approach: A survey form assessing the specified concepts was designed and employed to examine the structural relationships. The research participants were international spectators ( n =512) attending the event. Data were randomly split into two halves, one for EFA ( n =256) and the other for CFA and SEM ( n =256). Findings: Findings revealed that core product feature and sport fan identification factors were significantly ( p <0.05) related to both of international spectators' desire to stay at the event, attend the event in the future, and revisit the country; whereas, event operation quality was only found to be significantly influential of the re-patronage, and destination image was only significantly influential of the desire to stay. The findings highlight the importance and relevance of these concepts in attracting, serving, and retaining international visitors to the event. Originality/value: Unlike other studies that are centered merely on game and event factors, this study expanded on a bigger ecological spectrum surrounding a F1 event and systematically evaluated the critical concepts and factors affecting international tourist to the event that can be considerable sources of economic growth. The findings provide empirical evidence for event and tourism management and marketing.